The Effect of Visualization on Students’ Understanding of Probability Concepts - Vargas, John M.; Starns, Jeffrey J.; Cohen, Andrew L.; Earnest, Darrell (Journal of statistics and data science education, 2025)
Bayesian reasoning - the optimal process of updating a hypothesis or belief with new information - is a critical aspect of both everyday decision-making and statistics education, but strategies for effectively teaching the topic in the classroom remain elusive. This study leverages the findings of prior research on facilitating Bayesian reasoning by utilizing a visualization, called the bar display, as a method for teaching Bayes theorem and its underlying probability concepts. Data were collected from a college-level statistics-in-psychology course, wherein students were taught and tested on Bayesian reasoning either with or without the bar display. In addition to testing the immediate efficacy of the bar display, data were also collected to test long-term retention and the potential differential benefits for low numeracy and high anxiety students. Results indicated engagement with the bar display as a method for visually approximating answers to Bayesian questions, with students trained with the bar display providing more accurate answers to Bayesian reasoning questions before training and at long-term assessment. Additionally, students with self-reported low numeracy and high math anxiety performed better on Bayesian reasoning questions when learning with the bar display. Recommendations for future implementations are discussed.